2021
DOI: 10.1038/s41598-021-92445-z
|View full text |Cite
|
Sign up to set email alerts
|

SIRT2 promotes murine melanoma progression through natural killer cell inhibition

Abstract: SIRT2, an NAD+-dependent histone deacetylase, has been shown to play a pivotal role in various physiological processes, however, its role in cancer is currently controversial. In recent years, SIRT2 has been described as both a tumor suppressor and oncogene with divergent expression and function in various malignancies. Using murine allograft melanoma models, our results suggest increased systemic expression of SIRT2 promotes tumor progression. In this study, SIRT2-overexpressing mice exhibited enhanced tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 61 publications
(69 reference statements)
1
13
0
Order By: Relevance
“…ese results confirm those of previous studies, in which SIRT2 expression level and CD8+ T cell infiltration level were positively correlated in breast cancer patients [51]. In addition, systemic SIRT2 has been suggested to promote tumor development by suppressing NK cells [42]. Interestingly, SIRT2 expression was significantly lower in breast cancer than in normal breast tissue, suggesting that SIRT2 may act as a tumor suppressor during the initiation of tumorigenesis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…ese results confirm those of previous studies, in which SIRT2 expression level and CD8+ T cell infiltration level were positively correlated in breast cancer patients [51]. In addition, systemic SIRT2 has been suggested to promote tumor development by suppressing NK cells [42]. Interestingly, SIRT2 expression was significantly lower in breast cancer than in normal breast tissue, suggesting that SIRT2 may act as a tumor suppressor during the initiation of tumorigenesis.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, it can greatly impact the e ectiveness of immunotherapy, highlighting the need of its further understanding [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic overexpression of SIRT2 promotes melanoma progression in immune-competent mice by suppressing the infiltration and function of NK cells in TME. Pharmacological inhibition of SIRT2 potentiates NK cell-dependent antitumor immunity and the growth of allograft melanoma ( 86 ), which might be of translational implication in increasing the efficacy of immunotherapy. Moreover, EZH2-mediated histone H3 methylation of HIF1α in macrophages leads to the silence of HIF1α expression and reprograms the immune suppressive microenvironment to the facilitative one, which alleviates the tumor burden and prolongs the overall survival of mice implanted with tumor ( 88 ).…”
Section: Epigenetics In Melanoma Antitumor Immunitymentioning
confidence: 99%
“…There have been no reports on the role of sirtuins in immunotherapy of esophageal cancer, although some reports have appeared in other cancer types. Zhang et al [ 115 ] showed that pharmacological inhibition of SIRT2 increased natural killer cell infiltration into the tumor and suppressed tumor growth in allograft melanoma. Furthermore, Xiang et al [ 116 ] demonstrated that SIRT7 suppressed myocyte enhancer factor 2D acetylation and programmed death ligand 1 expression and promoted HCC cell proliferation.…”
Section: Future Perspectivesmentioning
confidence: 99%